2018
DOI: 10.1111/pcmr.12762
|View full text |Cite|
|
Sign up to set email alerts
|

Local genomic features predict the distinct and overlapping binding patterns of the bHLH‐Zip family oncoproteins MITF and MYC‐MAX

Abstract: MITF and MYC are well‐known oncoproteins and members of the basic helix–loop–helix leucine zipper (bHLH‐Zip) family of transcription factors (TFs) recognizing hexamer E‐box motifs. MITF and MYC not only share the core binding motif, but are also the two most highly expressed bHLH‐Zip transcription factors in melanocytes, raising the possibility that they may compete for the same binding sites in select oncogenic targets. Mechanisms determining the distinct and potentially overlapping binding modes of these cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…The requirement for the flanking 5 ′ T-3 ′ A may be to restrict binding to many MITF recognition motifs by MYC, which has a preference for sites lacking the T-A flanking sequences, and other bHLH-LZ factors able to recognize similar 6-bp elements as heterodimers with MAX (Fisher et al 1993;Solomon et al 1993). Indeed, recent genome-wide analysis has confirmed that the flanking sequences represent major discriminators between MYC-MAX binding and MITF, although a restricted subset of E-box motifs is able to bind both MYC and MITF (Hejna et al 2018). Collectively, these studies indicate that sequence specificity of MITF means that it has a largely complementary repertoire of targets to MYC (Fig.…”
Section: Mitf Dna-binding Specificitymentioning
confidence: 99%
“…The requirement for the flanking 5 ′ T-3 ′ A may be to restrict binding to many MITF recognition motifs by MYC, which has a preference for sites lacking the T-A flanking sequences, and other bHLH-LZ factors able to recognize similar 6-bp elements as heterodimers with MAX (Fisher et al 1993;Solomon et al 1993). Indeed, recent genome-wide analysis has confirmed that the flanking sequences represent major discriminators between MYC-MAX binding and MITF, although a restricted subset of E-box motifs is able to bind both MYC and MITF (Hejna et al 2018). Collectively, these studies indicate that sequence specificity of MITF means that it has a largely complementary repertoire of targets to MYC (Fig.…”
Section: Mitf Dna-binding Specificitymentioning
confidence: 99%
“…It also suppresses senescence ( Giuliano et al., 2010 ). Like other bHLH or bHLH-LZ family members, MITF recognizes 6-bp E-box motifs, with flanking sequences permitting MITF and other E-box-binding factors to discriminate between related target sites ( Aksan and Goding, 1998 , Blackwell and Weintraub, 1990 , Fisher et al., 1993 , Fisher and Goding, 1992 , Hejna et al., 2019 , Solomon et al., 1993 ). Despite the key role of MITF in melanoma progression, surprisingly little is known about how its target gene selectivity is modulated.…”
Section: Introductionmentioning
confidence: 99%
“…These distinct advantages of the BCDT model over the CNN model are particularly important in situations such as protein-DNA interaction prediction where extracting the biologically relevant information from the model is just as important as maximizing prediction accuracy. Along this line, we have recently demonstrated the utility of our method in the context of learning biological sequence features that can help distinguish the in-vivo binding patterns of two important oncogenic transcription factors in the same protein family (Hejna et al, 2019).…”
Section: Discussionmentioning
confidence: 98%